FlAsH-based live-cell fluorescent imaging of synthetic peptides expressed in Arabidopsis and tobacco. (November 2006) - Estévez, José M.; Somerville, Chris
Genes encoding synthetic hydroxyproline-rich peptides with repetitive (Ser-Pro) units linked to an extensin signal sequence and a tetracysteine (TC) sequence were expressed transiently in tobacco, and transiently and stably in Arabidopsis under control of a strong constitutive promoter. Expression of these peptides could be visualized in live cells by confocal microscopy following labeling with FlAsH- or ReAsH-EDT2 reagents.